SI-MAMAS : Design and Development of a Mobile-Based Mosque Management Information System - Alda, Muhamad (ULTIMATICS, 2025)
The Nurul Huda Mosque is one of the mosques in the city of Medan. So far, the Nurul Huda Mosque has not provided a facility or media that can be used to manage data, such as management data, financial data, activity data, and inventory data. The data management process is still carried out conventionally on a book, so several problems still occur, especially regarding data completeness, data damage, and loss of data that has been processed. The aim of this research is to build a mobile-based information system that can be used to manage mosque data. In building the information system, the author used the Rapid Application Development (RAD) method, which consists of planning stages, design workshops, and implementation. Meanwhile, the tool used by the author in creating information system designs visually is UML (Unified Modeling Language). The mobile-based information system was built using the Kodular framework and the Airtable database. With this information system, it is hoped that it can help the Nurul Huda Mosque process data easily and quickly via an Android smartphone.